Tetrabutylammonium methacrylate as a novel receptor for selective extraction of sulphonylurea drugs from biological fluids using molecular imprinting. Issue 43 (6th October 2015) - Hasanah, A. N.; Pessagno, F.; Kartasasmita, R. E.; Ibrahim, S.; Manesiotis, P.
Abstract : Tetrabutylammonium methacrylate introduced as functional monomer for the stoichiometric imprinting of sulfonylurea drug glibenclamide. Abstract : Glibenclamide (GLIB), an oral antidiabetic medication of the sulphonylurea drug family, was stoichiometrically imprinted using tetrabutylammonium methacrylate as the functional monomer, for the first time in molecular imprinting, and utilising the sulphonylurea affinity for carboxylate anions. Solution association between the drug and the novel functional monomer was studied by 1 H-NMR titrations, whereby evidence of sulphonylurea deprotonation followed by the formation of "narcissistic" GLIB dimers was found when tested in CDCl3, while an affinity constant in excess of 10 5 L mol −1 was measured in DMSO-d6 . Detailed analysis of GLIB binding on the subsequently prepared imprinted and non-imprinted polymers confirmed the deactivation of binding sites by exchange of a proton between GLIB and methacrylate, followed by extraction of the tetrabutylammonium counterion from the polymer matrix, resulting in overall reduced binding capacities and affinities by the imprinted material under equilibrium conditions. An optimised MI-SPE protocol, which included a binding site re-activation step, was developed for the extraction of GLIB from blood serum, whereby recoveries of up to 92.4% were obtained with an exceptional sample cleanup.